Cloud Transformation Challenges: Do They Favor the Emergence of Low-Code and No-Code Platforms - Puri, Amit (Digital Repository of Theses, 2025)
This research investigates the challenges associated with cloud transformation and explores whether these challenges create a conducive environment for the emergence of low-code and no-code (LCNC) platforms as viable solutions for digital innovation. The study focuses on cloud-native development strategies, cloud migration models, and the growing role of LCNC platforms in enabling faster application development and deployment. Methodologically, this research applies both qualitative and quantitative approaches, comparing traditional custom development models with LCNC solutions. Key metrics evaluated include cost efficiency, scalability, deployment control, and business process automation. Additionally, the research delves into the integration of advanced technologies like artificial intelligence (AI) and machine learning (ML) within LCNC platforms, assessing their impact on accelerating digital transformation efforts. The findings suggest that cloud transformation often faces significant hurdles, particularly in handling complex workloads and legacy systems. These challenges have fueled the rise of LCNC platforms, which offer a more accessible and efficient alternative for both technical and non-technical users. LCNC platforms have proven to be instrumental in reducing development time and cost, facilitating rapid prototyping, and improving operational efficiency through automation. However, the research also highlights limitations, including customisation constraints and concerns about scalability in large enterprises. In conclusion, while LCNC platforms present a compelling solution for overcoming cloud transformation challenges, their widespread adoption will require addressing issues related to platform scalability, vendor lock-in, and the integration of open standards. Nonetheless, these platforms are poised to play a pivotal role in future digital transformation initiatives, empowering businesses to innovate and scale rapidly in an increasingly competitive landscape.